Práticas laboratoriais envolvendo o jogo de xadrez - Oliveira, Joabe Gileade da Silva (Universidade Federal Rural do Semi-Árido, 2019)
In view of the challenging reality of learning in mathematics in our country and the perspectives and trends of mathematics education, as well as the importance of the use of concrete material in mathematics labs and the urgent need to make mathematical knowledge meaningful to the Brazilian student by This work showed the use of the strategic game of chess as a powerful tool for practical laboratory classes in mathematics and described 30 successful practices that were divided into two parts, namely: the first part of the research had as objective to present the game of chess and to develop the students' deductive logical reasoning from situations - problem intrinsic to the game. The second part turned to the presentation of several mathematical themes through the pieces and the chessboard
Keywords: Ensino; Aprendizagem; Jogo; Matemática; Xadrez; Teaching; Learning; Game; Mathematics; Chess; CIENCIAS EXATAS E DA TERRA::MATEMATICA